Integration of Ca-Looping Systems for CO2 Capture in Cement Plants. (July 2017) - Spinelli, M.; Martínez, I.; De Lena, E.; Cinti, G.; Hornberger, M.; Spörl, R.; Abanades, J.C.; Becker, S.; Mathai, R.; Fleiger, K.; Hoenig, V.; Gatti, M.; et al.
Abstract: Ca-Looping (CaL) has been demonstrated as a promising technology for CO2 capture in coal-fired power plants. A promising application is also in cement plants, where the CaO-rich material purged from the CaL process can replace part or all of the raw material used for clinker production. The aim of this work is to investigate two process integration options of the CaL system based on fluidized bed and entrained flow reactors in a clinker burning process. The main advantages, constrains and research questions of the two configurations are discussed, and the mass and energy balances of the whole processes are detailed and analyzed.